Lost in translation: The challenge of Javanese students in pronouncing English consonant sounds - Tarbiyah, Shofwatut; Mahfudza, Fitria Zulaika; Rohmana, Wahyu Indah Mala (Proceeding of International Conference on Islamic Education (ICIED), 2025)
Pronunciation difficulties in English often arise due to differences in the phonological system between English and the speaker’s mother tongue. One of the problematic consonant clusters for Indonesian learners, particularly those with strong Javanese accents, is the “gh” sound, which varies in pronunciation depending on the word. This research aims to explore the challenge by Javanese students in pronouncing three variations of “gh”: silent “gh,” “gh” pronounced as [f], and [g]. This research employed a qualitative descriptive method. Data were collected through observation and a pronunciation test using a list of 20 English words containing three types of “gh” pronunciation. To gain deeper analysis, structured interviews consisting of five questions were conducted with four students who have strong Javanese accents. The results indicate that the silent “gh” is the most difficult form to pronounce, while the [f] is the easiest for most participants. The [g] variant ranks in between. The main influencing factor is the strong interference of the Javanese mother tongue. These findings suggest that pronunciation teaching for Javanese learners should explicitly emphasize the three “gh” patterns, especially the silent form, and incorporate targeted drilling and minimal-pair practice to reduce first-language interference.